Bumblebees (Bombus terrestris) forage on plants treated with glyphosate-based herbicides despite potential behavioral consequences - Kimmo Kaakinen; Satu Ramula; Benjamin Fuchs; James D. Blande; Eva-Maria Vaajamo; Marjo Helander (Environmental Research, 2025)

Plant metabolic responses to soil herbicide residues differ under herbivory in two woodland strawberry genotypes - Benjamin Fuchs; Marjo Helander; Kari Saikkonen; Petre I. Dobrev; Radomira Vankova; James D. Blande; Juha-Pekka Salminen; Niko Luntamo; Anne Muola (Science of The Total Environment, 2024)

The effects of short-term glyphosate-based herbicide exposure on insect gene expression profiles - Miia J. Rainio; Aigi Margus; Santtu Tikka; Marjo Helander; Leena Lindström (Journal of Insect Physiology, 2023)

Ecosystem consequences of herbicides: the role of microbiome - Suvi Ruuskanen; Benjamin Fuchs; Riitta Nissinen; Pere Puigbò; Miia Rainio; Kari Saikkonen; Marjo Helander (Trends in Ecology & Evolution, 2023)

Field-realistic acute exposure to glyphosate-based herbicide impairs fine-color discrimination in bumblebees - Marjo Helander; Topi K. Lehtonen; Kari Saikkonen; Léo Despains; Danae Nyckees; Anna Antinoja; Cwyn Solvi; Olli J. Loukola (Science of The Total Environment, 2023)

Insect herbivory may cause changes in the visual properties of leaves and affect the camouflage of herbivores to avian predators - Tuuli-Marjaana Koski; Carita Lindstedt; Tero Klemola; Jolyon Troscianko; Elina Mäntylä; Esa Tyystjärvi; Martin Stevens; Marjo Helander; Toni Laaksonen (Behavioral Ecology and Sociobiology, 2017)

No effects of Epichloë endophyte infection on nitrogen cycling in meadow fescue (Schedonorus pratensis) grassland - Juha Mikola; Marjo Helander; Kari Saikkonen (Plant and Soil, 2016)

Endophytic Epichloë species and their grass hosts: from evolution to applications - Kari Saikkonen; Carolyn A. Young; Marjo Helander; Christopher L. Schardl (Plant Molecular Biology, 2016)

Nutritional niche overlap potentiates the use of endophytes in biocontrol of a tree disease - Kathrin Blumenstein; Benedicte R. Albrectsen; Juan A. Martín; Malin Hultberg; Thomas N. Sieber; Marjo Helander; Johanna Witzell (BioControl, 2015)

Chemical Ecology Mediated by Fungal Endophytes in Grasses - Kari Saikkonen; Pedro E. Gundel; Marjo Helander (Journal of Chemical Ecology, 2013)

Antioxidants in Festuca rubra L. seeds affected by the fungal symbiont Epichloë festucae - Pedro E. Gundel; Cyd E. Hamilton; Charlotte E. Seal; Marjo Helander; María Alejandra Martínez-Ghersa; Claudio M. Ghersa; Beatriz R. Vázquez de Aldana; Iñigo Zabalgogeazcoa; Kari Saikkonen (Symbiosis, 2012)

Phenolic Compounds of the Inner Bark of Betula pendula: Seasonal and Genetic Variation and Induction by Wounding - Jaana Liimatainen; Maarit Karonen; Jari Sinkkonen; Marjo Helander; Juha-Pekka Salminen (Journal of Chemical Ecology, 2012)

Variable effects of endophytic fungus on seedling establishment of fine fescues - Piippa R. Wäli; Marjo Helander; Irma Saloniemi; Jouni Ahlholm; Kari Saikkonen (Oecologia, 2009)

Consumption of grass endophytes alters the ultraviolet spectrum of vole urine - Otso Huitu; Marjo Helander; Päivi Lehtonen; Kari Saikkonen (Oecologia, 2008)

Transfer of endophyte‐origin defensive alkaloids from a grass to a hemiparasitic plant - Päivi Lehtonen; Marjo Helander; Michael Wink; Frank Sporer; Kari Saikkonen (Ecology Letters, 2005)
Plants growing in natural environments experience myriad interactions with a diverse assemblage of pathogens, parasites and mutualists. Many of these interactions involve symbiotic bacteria and fungi, but they also include macroparasitic plants. In this study, we investigated the interactions among a host grass ( Lolium pratense , ex., Festuca pratensis ), its symbiotic endophytic fungus ( Neotyphodium uncinatum ), a root hemiparasitic plant ( Rhinanthus serotinus ) of the host grass and a generalist herbivore (aphid Aulacorthum solani ) of the hemiparasite. We demonstrate that the hemiparasitic plant acquires defending mycotoxins produced by the endophytic fungus living within their shared host grass. The uptake of defensive mycotoxins from the endophyte‐infected host grass enhances the resistance of the hemiparasitic plant to the generalist aphid herbivore. Endophyte infection increases the performance of the hemiparasitic plant, but reduces the growth of the host grass. In other words, the mutualistic endophytic fungus becomes parasitic in the presence of the hemiparasitic plant. Our results suggest that the outcomes of grass–endophyte interactions are conditional on the complexity of community‐level interactions; thus, the outcome of multispecies interactions may not be predictable from pair‐wise combinations of species.

Leaf surface traits: overlooked determinants of birch resistance to herbivores and foliar micro-fungi? - Elena Valkama; Julia Koricheva; Juha-Pekka Salminen; Marjo Helander; Irma Saloniemi; Kari Saikkonen; Kalevi Pihlaja (Trees, 2005)

Are endophyte-mediated effects on herbivores conditional on soil nutrients? - Pivi Lehtonen; Marjo Helander; Kari Saikkonen (Oecologia, 2005)

Asexual Neotyphodium endophytes in a native grass reduce competitive abilities - Stanley H. Faeth; Marjo L. Helander; Kari T. Saikkonen (Ecology Letters, 2004)
Asexual, vertically transmitted endophytes are well known for increasing competitive abilities of agronomic grasses, but little is known about endophyte–host interactions in native grasses. We tested whether the asexual Neotyphodium endophyte enhances competitive abilities in a native grass, Arizona fescue, in a field experiment pairing naturally infected (E+) and uninfected (E−) plants, and in a greenhouse experiment pairing E+ and E− (experimentally removed) plants, under varying levels of soil water and nutrients. In the field experiment, E− plants had greater vegetative, but not reproductive, growth than E+ plants. In the greenhouse experiment, where plant genotype was strictly controlled, E− plants consistently outperformed their E+ counterparts in terms of root and shoot biomass. Thus, Neotyphodium infection decreases host fitness via reduced competitive properties, at least in the short term. These findings contrast starkly with most endophyte studies involving introduced, agronomic grasses where infection increases competitive abilities, and the interaction is viewed as highly mutualistic.

Micro‐fungi and invertebrate herbivores on birch trees: fungal mediated plant–herbivore interactions or responses to host quality? - Jouni Ahlholm; Marjo Helander; Pirjo Elamo; Irma Saloniemi; Seppo Neuvonen; Sinikka Hanhimäki; Kari Saikkonen (Ecology Letters, 2002)
We studied interactions between microfungi and herbivores sharing a host tree. In a series of experiments and field observations over a 3‐year period, we compared phenotypic and genetic correlations of fungal frequencies and performance of invertebrate herbivores growing on mature half‐sib progenies of mountain birches ( Betula pubescens ssp. czerepanovii ) in two environments, a forested river valley and an adjacent higher‐elevation mountain birch woodland. We found little support for direct relation between fungal frequencies and performance of herbivore species. Instead, genetic correlations, particularly between autumnal moth ( Epirrita autumnata ) and rust fungus ( Melampsoridium betulinum ), suggest that herbivore performance may be caused by (1) genetic differences in plant quality for fungi and herbivores, or (2) genetic differences in responses to environmental conditions.

Birch family and environmental conditions affect endophytic fungi in leaves - Pirjo Elamo; Marjo L. Helander; Irma Saloniemi; Seppo Neuvonen (Oecologia, 1999)

Variation in airborne urediniospore concentration ofMelampsoridium betulinum - Pirjo Vuorinen; Marjo L. Helander (Aerobiologia, 1995)

Birch pollen production, transport and deposition for the period 1984–1993 at Kevo, northernmost Finland - Sheila Hicks; Marjo Helander; Saini Heino (Aerobiologia, 1994)

Circadian periodicity of airborne pollen and spores; significance of sampling height - Aulirantio-Lehtimäki; Marjo Linnea Helander; Anna-Mari Pessi (Aerobiologia, 1991)

Comparison of some pollen concentrations in Finland and the Estonian SSR - Ritva Kupias; Marjo Linnea Helander; Maret Saar; Yrjö Mäkinen (Aerobiologia, 1989)